2022
DOI: 10.3389/fcimb.2021.767306
|View full text |Cite
|
Sign up to set email alerts
|

Filarial Lymphedema Patients Are Characterized by Exhausted CD4+ T Cells

Abstract: Worldwide, more than 200 million people are infected with filariae which can cause severe symptoms leading to reduced quality of life and contribute to disability-adjusted life years (DALYs). In particular, lymphatic filariasis (LF) caused by Wuchereria bancrofti can lead to lymphedema (LE) and consequently presents a serious health problem. To understand why only a fraction of the infected individuals develop pathology, it is essential to understand how filariae regulate host immunity. The central role of T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…In this study, a small subset of filarial LE participants from Ghana ( n = 25) was initially sampled and compared with uninfected control ( n = 34) and Wb-infected ( n = 10) individuals. This same participant cohort was recently seen to display distinct patterns of exhausted effector and memory CD4 + and CD8 + T cell subsets and, thus, we were interested in determining if they also displayed altered activation profiles, since T cell exhaustion is often caused by immune activation, persistent antigen stimulation, and inflammation [ 17 , 18 , 25 , 26 ]. Building on our previous analysis, we conducted a more in-depth evaluation of immune activation patterns in filarial lymphedema participants with different stages by including more participants from two different study sites; we showed that there is indeed an increase in systemic CD4 + T cell activation associated with the progression of chronic LE within a relatively large cohort of LE participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, a small subset of filarial LE participants from Ghana ( n = 25) was initially sampled and compared with uninfected control ( n = 34) and Wb-infected ( n = 10) individuals. This same participant cohort was recently seen to display distinct patterns of exhausted effector and memory CD4 + and CD8 + T cell subsets and, thus, we were interested in determining if they also displayed altered activation profiles, since T cell exhaustion is often caused by immune activation, persistent antigen stimulation, and inflammation [ 17 , 18 , 25 , 26 ]. Building on our previous analysis, we conducted a more in-depth evaluation of immune activation patterns in filarial lymphedema participants with different stages by including more participants from two different study sites; we showed that there is indeed an increase in systemic CD4 + T cell activation associated with the progression of chronic LE within a relatively large cohort of LE participants.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 is a chemokine that has classically been known as a common co-receptor for HIV on CD4 + T cells, but it also plays a role in other bacterial, viral, and parasitic infections [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. While there have been few studies examining the profile of CCR5 and other chemokines in relation to filarial LE, our group previously examined the frequencies of CCR5 and an array of memory markers among a Ghanaian cohort of individuals that suffer from LE in comparison to other non-LE individuals residing in filarial endemic areas [ 17 , 18 ]. We saw evidence of higher frequencies of CD8 + CCR5 + per se, as well as increased frequencies of CCR5 + CD45RA − memory T cells among the LE group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In detail, the immunological characterizations of W. bancrofti -infected, LE and EN individuals show that W. bancrofti (e.g., CFA+MF+ individuals) induce increased levels of regulatory T (Treg) and B cells (Breg) in the peripheral blood accompanied by regulatory and type 2 immune responses including IL-10, IL-4, IL-5, TGF-β and IgG4 [ 5 , 8 , 9 , 10 , 11 , 12 ]. In contrast, LE individuals are associated with enhanced Th1, Th17 and pro-inflammatory responses [ 12 , 13 , 14 , 15 , 16 ], and harbor exhausted T cell populations in peripheral blood [ 17 , 18 ]. However, reports about the immunological characterization of individuals who cleared the infection (PI; previously infected individuals) due to MDA are sparse.…”
Section: Introductionmentioning
confidence: 99%